Trimetallic Metal‐Organic Framework Nanoframe Superstructures: A Stress‐Buffering Architecture Engineering of Anode Material toward Boosted Lithium Storage Performance. Issue 1 (22nd March 2022) - Lin, Jia; Xu, Chao; Lu, Man; Lin, Xiaoming; Ali, Zeeshan; Zeng, Chenghui; Xu, Xuan; Luo, Yifan
Abstract : Metal‐organic frameworks (MOFs) can serve as prevailing anodes for lithium‐ion batteries, due to their multiple redox‐active sites and prominent structural compatibility. However, the poor electronic conductivity and inferior cyclability hinder their further implementation. Herein, a synthetic methodology for trimetallic Fe‐Co‐Ni MOFs with nanoframe superstructures architecture (Fe‐Co‐Ni NFSs) via structural evolution is proposed for versatile anode materials for lithium storage. Ascribed to optimal compositional and structural optimization, the Fe‐Co‐Ni NFSs achieve exceptional electrochemical performance with superior specific capacity (1030 mAh g −1 at 0.1 A g −1 ), outstanding rate capacity (414 mAh g −1 at 2 A g −1 ), and prolonged cyclability (489 mAh g −1 upon 1000 cycles at 1 A g −1 ). Both experimental and theoretical investigations reveal that the multi‐component metal centers could boost electronic conductivity, confer multiple active sites, and energetically favor Li adsorption capability. Additionally, the nanoframe superstructures of Fe‐Co‐Ni NFSs could facilitate stress‐buffering effect on volumetric expansion and prevent electrode pulverization, further improving the lithium storage capability. This work envisions a meticulous protocol for high‐performance MOF anode materials for lithium‐ion batteries. Abstract : A synthetic methodology for trimetallic Fe‐Co‐Ni metal‐organic frameworks with nanoframe superstructures architecture (Fe‐Co‐Ni NFSs) is proposed for versatile anode material toward lithium storage. Enlightened by experimental and theoretical investigations, the Fe‐Co‐Ni NFSs achieves exceptional electrochemical performance (inciting specific capacity, fabulous rate capacity, and pre‐eminent cyclability), ascribing to the optimal compositional and structural complementarity.